Efektivitas Manajemen Pendidik dan Tenaga Kependidikan dalam Meningkatkan Mutu Pendidikan di SMK Negeri 1 Surabaya - Nawangsari, Dewi Cantika; Farihah, Azza Atiqotul Maula Al; Windasari, Windasari; Cindy, Agustin Hanifa (TSAQOFAH, 2024)
This article analyzes the effectiveness of the management of educators and education personnel in improving the quality of education at SMK Negeri 1 Surabaya. Management of educators and education personnel is one of the efforts made by the Education Office in achieving educational goals to create superior generations of successors in facing the current technological era. Improving the quality of educators and education personnel is needed so that the process of implementing learning and teaching activities in an educational institution can run optimally and efficiently. The method used in this research is descriptive qualitative which focuses on data collection techniques by conducting interviews with selected sources. The results of this study indicate the effectiveness of management carried out in improving the quality of teaching and education personnel at SMK Negeri 1 Surabaya.